AN INVESTIGATION INTO LINGUISTIC FEATURES OF PERSUADING AS A SPEECH EVENT IN ENGLISH AND VIETNAMESE - NGUYỄN ĐĂNG KHOA (Trường Đại học Ngoại ngữ, 2025)
This study investigates the strategies of persuading and responding in English and Vietnamese. We look at the conventional markers of the persuasions, the generalizations of the linguistic realizations of the indirect persuasions, the preparatory work prefacing the persuasions and the responses, identifying the similarities and differences between these two languages. The results of the study make it possible to locate the areas which might prove to be difficult to the Vietnamese learners of English. On this basis, a number of persuasions are put forward for the teaching of the strategies of persuading and responding in English to the Vietnamese learners in terms of the teaching material and the activities in the class.